Respuesta :
Answer:
n = -3
(second option listed)
Step-by-step explanation:
first, we will distribute the 11 (n-1)
11 (n - 1) + 35 = 3n
11n - 11 + 35 = 3n
Now, we will combine -11 and 35 (because they are like terms)
11n + 24 = 3n
Now, to isolate x as a positive, I will subtract 3n from both sides
11n + 24 = 3n
- 3n - 3n
8n + 24 = 0
Now, I will subtract 24 from both sides to isolate n
8n + 24 = 0
- 24 - 24
8n = -24
Now, we will divide both sides by 8 to find "n"
8n = -24
÷8 ÷8
n = -3
This means that n is equal to -3
(n = -3)
Answer: B) n = -3
Step-by-Step Explanation:
11(n - 1) + 35 = 3n
11 * n - 11 * 1 + 35 = 3n
11n - 11 + 35 = 3n
11n + 24 = 3n (Shift +3n to LHS)
11n - 3n + 24 = 0 (Shift +24 to RHS)
11n - 3n = -24
8n = -24 (Shift *8 to RHS)
n = -24/8
=> n = -3
Therefore, n = -3
Step-by-Step Explanation:
11(n - 1) + 35 = 3n
11 * n - 11 * 1 + 35 = 3n
11n - 11 + 35 = 3n
11n + 24 = 3n (Shift +3n to LHS)
11n - 3n + 24 = 0 (Shift +24 to RHS)
11n - 3n = -24
8n = -24 (Shift *8 to RHS)
n = -24/8
=> n = -3
Therefore, n = -3